Break Even Point (BEP) Analysis and Selling Price Sensitivity to the Sustainability of Hydroponic Beef Tomato Business in the Lembang Region - Indri Utami; Uswatun Hasanah; Puti Harissa Pratidina (Business Management, 2026)
The sustainability of hydroponics-based horticulture businesses, especially beef tomatoes, is greatly influenced by the ability of business actors to manage financial aspects and deal with market price fluctuations. Financial feasibility analysis is an important instrument in assessing the ability of hydroponic horticulture businesses to survive and develop in the midst of production cost dynamics and market prices. This study aims to analyze the financial feasibility of the hydroponic beef tomato business through the Break Even Point (BEP) approach and to assess the level of business sensitivity to changes in selling prices. The study used a descriptive quantitative method with primary data obtained through a questionnaire to hydroponic tomato beef business actors in the Lembang area. The data analyzed includes fixed costs, variable costs, selling prices, and production volume per business cycle. The results of the study show that most of the hydroponic tomato beef businesses have reached break-even at a lower production level compared to actual production, so that in general the business is in a decent financial condition. However, there are several business actors who have not yet reached break-even conditions due to the high variable cost per unit of product compared to the selling price. The analysis of selling price sensitivity shows that a price decrease of 10-15 percent has a significant impact on increasing break-even and has the potential to reduce business sustainability, while an increase in selling price provides greater profit room and increases the financial resilience of the business. This study concludes that production cost control and adaptive pricing strategies are key factors in maintaining the sustainability of the hydroponic beef tomato business. The research findings are expected to be the basis for decision-making for business actors and stakeholders in designing sustainable hydroponic horticulture business management strategic.